Maternal Stress and Anxiety as Predictors of Mental Health among Pregnant Women in Port Harcourt Metropolis, Nigeria - Enyelunekpo R. Roberts; Chinenye A. Ezenwora; Olubunmi O. James; Emmanuel E. Uye (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
Mental health among pregnant women continues to be issues of concern to reproductive health professionals. Studies examining mental health among women produced varying results. Therefore, the purpose of this study was to examine the predictive ability of maternal stress and anxiety on mental health among pregnant women Cross-sectional survey design was adopted while purposive sampling technique was used to select the study population. Data were collected from 250 pregnant women using a validated scale and analyzed using multiple regression analysis to test an hypothesis which was accepted at p =.001 level of significance. The result showed that maternal stress and anxiety jointly predicted mental health among study participants (R2 = .049, F( 2 , 247) = 6.313 , p < .01). Moreover, maternal stress independently predicted mental health among study participants (β = .209, t = 3.37, p <.01). However, anxiety did not independently predict mental health among study participants (β = .18, t = 1.31, p >.05). The study concludes that the interaction of maternal stress and anxiety are strong predictors of mental health among pregnant women in the study samples. It is recommended that mental health professionals should organize cognitive behavioral counselling to help women during pregnancy. Abstrak Kesehatan mental di antara wanita hamil terus menjadi masalah yang menjadi perhatian bagi para profesional kesehatan reproduksi. Studi yang meneliti kesehatan mental di antara wanita menghasilkan hasil yang bervariasi. Oleh karena itu, tujuan dari penelitian ini adalah untuk meneliti kemampuan prediktif stres dan kecemasan ibu terhadap kesehatan mental di antara wanita hamil. Desain survei cross-sectional diadopsi sementara teknik purposive sampling digunakan untuk memilih populasi penelitian. Data dikumpulkan dari 250 wanita hamil menggunakan skala yang divalidasi dan dianalisis menggunakan analisis regresi berganda untuk menguji hipotesis yang diterima pada tingkat signifikansi p = 0,001. Hasil penelitian menunjukkan bahwa stres dan kecemasan ibu secara bersama-sama memprediksi kesehatan mental di antara peserta penelitian (R2 = 0,049, F (2, 247) = 6,313, p <0,01). Selain itu, stres ibu secara independen memprediksi kesehatan mental di antara peserta penelitian (β = 0,209, t = 3,37, p <0,01). Namun, kecemasan tidak secara independen memprediksi kesehatan mental di antara peserta penelitian (β = 0,18, t = 1,31, p > 0,05). Studi ini menyimpulkan bahwa interaksi antara stres dan kecemasan ibu merupakan prediktor kuat kesehatan mental di kalangan ibu hamil dalam sampel studi. Disarankan agar profesional kesehatan mental menyelenggarakan konseling perilaku kognitif untuk membantu ibu selama kehamilan. Kata Kunci: stres ibu; kecemasan; kesehatan mental; wanita hamil